Розвиток черевоногих молюсків у крейдяному періоді (Волино-Подільський сегмент Мезотетису) - Бакаєва, С. (Геологія і геохімія горючих копалин, 2010)
На підставі дослідження різновікових угруповань черевоногих молюсків, які
існували в межах Волино-Подільської ділянки крейдяного басейну, з’ясовано залежність розвитку цієї групи від палеогеографічних умов та їхніх змін. Виявлено,
що найсприятливіші умови для розвитку черевоногих виникали на початкових стадіях трансгресії і на завершальних стадіях регресії та позначилися в розрізах найчисленнішими угрупованнями черевоногих сеноманського і маастрихтського віків.
Поглиблення палеобасейну та встановлення стабільної глибоководної седиментації
з одночасним існуванням карбонатно-мулистого дна були несприятливими для розвитку черевоногих, тому в таких осадах їхні представники відсутні. Встановлено,
що найчисленніші угруповання черевоногих приурочені до відкладів субліторальної зони. Присутність у кожному з них фітофагів вказує на їхнє існування на малих
глибинах, у межах фотичної зони, де була достатня кількість рослинної їжі і детриту, а наявність інфауни та приуроченість до піщано-алевритових фацій – на не дуже
твердий піщано-глинистий субстрат дна. On the basis of the study of gastropods communities from Volyn-Podillya region the
changes of their ecological structure in Cretaceous have been considered. Relation between the group distribution and palaeogeographical conditions have been found out. The
optimal conditions for gastropod’s development has been arising during the initial stages
of transgression and final stages of regression. It had been stated in sections by numerous
communities of Cenomanian (36 species, 26 genera, 18 familiae) and Maastrichtian
(79 species, 35 genera, 24 familiae) ages. An increase of the sea depth and an establishment of stable deep-water sedimentation with a soft calcareous-muddy substrate were
disadvantageous to gastropod’s development, therefore their representatives in the sediments of such stages are absent. The most numerous communities of the study molluscs
are distributed within the sublittoral sediments. The high percent of phytophagan and infauna in each of them indicates a shallow water (inner shelf) rich in plant vegetation, and
not too firm sandy-argillaceous substrate.
Three phases of the development of gastropods fauna have been singled out and described. Albian-Cenomanian phase is characterized by the prevailing of gastropods from
families Pleurotomariidae and Trochidae. Avellana cassis, A. telegdii, Oolitica tuberculatocostata, Solariella sobetskiiare dominant species for this phase. During Turonian-Coniacian phase gastropods communities have not been developing within the study area of the
paleobasin. It has been concerned with the global changes of the biota evolution and regional palaeogeographical processes, which have led to disadvantageous conditions for
gastropods existence. Santonian-Maastrichtian phase is characterized by the prevailing of
families Aporrhaidae, Turritellidae, Cerithiidae and Volutidae. Dominant species for the
phase are Drepanocheilus substenoptera, Aporrhais pyriformis, Avellana inversestriata,
Cerithium binodosum, Calliomphalus (C.) inaequecostatus.